COVID-19 and sustainable development goals: A bibliometric analysis and SWOT analysis in Malaysian context. (January 2023) - Nilashi, Mehrbakhsh; Ali Abumalloh, Rabab; Mohd, Saidatulakmal; Nurlaili Farhana Syed Azhar, Sharifah; Samad, Sarminah; Hang Thi, Ha; Alghamdi, OA; Alghamdi, Abdullah
Highlights: A SWOT analysis of COVID-19 and Sustainable Development Goals (SDGs) is performed. A bibliometric analysis of previous works related to SDGs and the covid-19 crisis is performed. COVID-19 crisis has caused an unprecedented "income shock" that is assumed to prompt food insecurity. Abstract: The COVID-19 crisis has been a core threat to the lives of billions of individuals over the world. The COVID-19 crisis has influenced governments' aims to meet UN Sustainable Development Goals (SDGs); leading to exceptional conditions of fragility, poverty, job loss, and hunger all over the world. This study aims to investigate the current studies that concentrate on the COVID-19 crisis and its implications on SDGs using a bibliometric analysis approach. The study also deployed the Strengths, Weaknesses, Opportunities, and Threats (SWOT) approach to perform a systematic analysis of the SDGs, with an emphasis on the COVID-19 crisis impact on Malaysia. The results of the study indicated the unprecedented obstacles faced by countries to meet the UN's SDGs in terms of implementation, coordination, trade-off decisions, and regional issues. The study also stressed the impact of COVID-19 on the implementation of the SDGs focusing on the income, education, and health aspects. The outcomes highlighted the emerging opportunities of the crisis that include an improvement in the health sector, the adoption of online modes in education, the swift digital transformation, and the global focus on environmental issues. Our study demonstrated that, in the post-crisis time, the ratio of citizens in poverty could grow up more than the current national stated values. We stressed the need to design an international agreement to reconsider the implementation of SDGs, among which, are strategic schemes to identify vital and appropriate policies.